Semiotika Al-Qur'an: Pembacaan Heuristic Dan Heurmenetic Michael Riffaterre Dalam Dialog Nabi Ibrahim Q.S Al-Anbiya’ 59-62 - Saleh, Sriwahyuningsih R; Doni, Chaterina Puteri; Pakaya, Nurul Aini (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2023)
This article discusses the semiotic study of the Quran using the heuristic and hermeneutic approaches developed by Michael Camille Riffaterre. The focus of the analysis is on Surah Al-Anbiya' verses 59-62, which narrate the story of Prophet Ibrahim and his struggle against idol worshipers. In the heuristic analysis, the research centers on understanding the surface text of the Quran, such as the dialogues and actions of Prophet Ibrahim and the reactions of the idol worshipers. This heuristic analysis reveals the chronology of events and actions of Prophet Ibrahim and underscores the importance of understanding the literal meaning of the Quranic text.Meanwhile, Riffaterre's hermeneutic analysis delves deeper into the hidden meanings and implications of this story. In these verses, there is symbolism that reflects a shift in the mindset of the idol worshipers as they come to realize their error. The consequences of misguided beliefs and the wisdom of worshiping Allah as the One and Only God become the moral message highlighted in this hermeneutic analysis.This semiotic study of the Quran provides a more comprehensive understanding of the story of Prophet Ibrahim and idol worship in the cultural and religious context of that time. The heuristic and hermeneutic approaches used by Riffaterre help unearth deeper meanings and relevant moral messages that can be applied in everyday life. Thus, this semiotic study strengthens the understanding of wisdom and truth in worshiping Allah as the one and only God